Feasibility and clinical benefit of a suture-mediated closure device for femoral vein access after percutaneous edge-to-edge mitral valve repair - Geis, Nicolas; Pleger, Sven Torsten; Chorianopoulos, Emmanuel; Müller, Oliver J.; Katus, Hugo; Bekeredjian, Raffi (EuroIntervention, 2015)
The Official Journal of EuroPCR and the European Association of Percutaneous Cardiovascular Interventions (EAPCI)
Published online ahead of print April 2014
Gesehen am 14.08.2020